Can ChatGPT Strengthen Students’ Confidence in Business Email Writing? A Quantitative Study of EFL Learners’ Self-Efficacy - Hindri Febri Ana Sari; Vascolino Pattipeilohy; Hedyan Putra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Despite increasing scholarly attention to generative artificial intelligence (AI) in language education, the extent to which ChatGPT supports learners’ confidence in workplace-oriented writing remains underexplored in EFL contexts. This study investigated the influence of ChatGPT-assisted instruction on EFL learners’ business email writing self-efficacy and explored students’ perceptions toward ChatGPT-mediated writing support. Using a quantitative quasi-experimental design, the study involved 70 sixth-semester students enrolled in a Business Letter course within a DIV Applied Business Administration Program at a state polytechnic in Ambon, Indonesia. Participants were assigned to an experimental group receiving ChatGPT-assisted instruction and a control group receiving conventional instruction during a 12-week intervention. Data were collected using a 30-item questionnaire and analysed through descriptive statistics, paired-samples t-tests, and independent-samples t-tests. The findings indicated substantially greater improvement in business email writing self-efficacy among students receiving ChatGPT-assisted instruction (mean gain = 19.40) than those receiving conventional instruction (mean gain = 6.26). Students also reported favorable perceptions regarding ChatGPT’s usefulness, revision support, confidence enhancement, anxiety reduction, and writing independence. The findings suggest that pedagogically mediated ChatGPT integration may serve as a meaningful resource for strengthening confidence in workplace-oriented EFL writing.